Bivalent interaction through an intrinsically disordered linker promotes transcription activation complex assembly in Notch signaling - Cyril Cook; Kristen M. Ramsey; Doug Barrick (Proceedings of the National Academy of Sciences, 2025)
The Notch signaling pathway regulates cellular differentiation by activating transcription through an unusual heterotrimeric complex comprising the Notch receptor’s intracellular domain (NICD), the DNA-binding protein CSL, and the coactivator MAML. NICD has two binding sites for CSL, a short motif in the RAM region and an ankyrin domain (ANK), connected by an intrinsically disordered linker and which form a bivalent ternary complex with CSL and MAML. Although bivalency is required for maximal transcription activation, the energetic contributions of bivalency and heterotrimer formation within this essential complex are unknown. To elucidate the energetics of bivalency, we first determine the free energy of the CSL-ANK-MAML heterotrimer, using isothermal titration calorimetry and developing an obligate heterotrimer model to analyze the data. By comparing this heterotrimerization reaction with binding reactions involving different regions of RAMANK, we determine the energetic contribution of bivalency to heterotrimer assembly. We show that bivalency through the disordered linker increases the effective concentration of ANK, and that the bivalent interaction enhances occupancy of RAM and ANK at their binding sites on CSL by about three orders of magnitude. By redefining the standard state to a lower, more physiological protein concentration, we reveal the importance of the RAMANK intrinsically disordered linker for assembly of the Notch transcription activation complex. This work provides a framework whereby the energetic contributions of intrinsically disordered linkers to higher-order multivalent assembly may be analyzed.